Formal techniques for distributed objects, components, and systems : 38th IFIP WG 6.1 International Conference, FORTE 2018, held as part of the 13th International Federated Conference on Distributed Computing Techniques, DisCoTec 2018, Madrid, Spain, June 18-21, 2018, proceedings /: 38th IFIP WG 6.1 International Conference, FORTE 2018, held as part of the 13th International Federated Conference on Distributed Computing Techniques, DisCoTec 2018, Madrid, Spain, June 18-21, 2018, proceedings. (2018) - Unknown
No abstract available